Social Media and Young Consumers Behavior - Jehangir Bharucha (International Journal of Supply Chain Management, 2018)
The Indian market is growing at an exponential rate. Social media is now getting increasingly widespread and popular with young consumers in India. Does social media affect consumer decision-making in India? Consumers do see a torrent of content from firms on social media but does this content benefit them? Data collection is achieved by using an online consumer survey of 145 social media users from the ages of 16 to 30 years The information was collected directly from respondents via the internet, from March 5th to May 16th, 2017.The influence of social media in Mumbai and other parts of India among the youth cannot be ignored. Although social media has myriad benefits for consumers, they all boil down to one thing: information. Consumers need information to make quick and reliable purchase decisions and social media has made this information available at their fingertips. Social media is also a form of expression for consumers and allows their voice to reach businesses and brands they usually purchase from. The study highlights several suggestions to businesses and social media platforms to optimize the advantages of social media for consumers through several ways and to consumers to enhance their social media experience.